Physical Condition Of Wrestling Athletes In West Java On PON XX - Papua 2021 - Eka Setiawati; Amung Ma’mun; Berliana Berliana (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
This study aims to determine and describe the development of the aerobic and anaerobic capacity of West Java women's wrestling athletes to face PON XX – 2021 Papua. This research method uses a quantitative descriptive method. The population in this study were women's wrestling athletes from West Java at PON XX 2021 Papua. The sampling technique used was non-probability with the purposive sampling technique. The number of samples in this study was 6 wrestling athletes from West Java. Data analysis used category percentages and factor analysis with the help of SPSS 23 software for windows. The results of this study indicate the physical condition of female wrestling athletes on cardio resistance in the first test was 39.48 ml/kg/min (79%) and in the second it was 39.51ml/kg/min (79%). The anaerobic component in the first test was 25.18 seconds (75.5%) and in the second test, it was 25.78 seconds (73.7%). The upper body endurance component in the first test is52.83 repetitions (81.3%), and on the second test 45.66 repetitions (71%). The component of abdominal muscle endurance in the first test is38.83 repetitions (59.7%), and on the second test 32 repetitions (49.2%). The leg power component in the first test is89%, and the second test of 85.1%. the agility component in the first test was 7.2 seconds (96.3%) and in the second test was 7.34 seconds (95.3%). The speed component in the first test was 3.81 seconds (86.7%) and in the second test was 3.77 seconds (87.6%). The flexibility component in the first test was 33.67 cm (112.2%), and in the second test was 41.33 cm (137.8%). Based on the factor analysis, the women's wrestling athlete from the West Java Regional National Sports Team at the Papua National Sports Week has a physical condition of 86.58%. In the first group, the percentage owned is 45.22% (speed). The second amount is 26.32% (cardio endurance and muscle endurance) Then the third amount is 15.04% (power, agility, flexibility). This study concludes that the overall components of the physical condition of the West Java women's wrestling athletes at the XX 2021 Papua PON are in the high category